HIGH PERCENTAGE OF YOUNG PEOPLE OF LIMA WORK, YOU KNOW YOU’RE SAVINGS IN THE AFP, WILL BE RETURNED AT THE TIME OF HIS RETIREMENT WITH VERY LOWER MONTHLY TO YOUR LAST SALARY EARNED - Barreda Guerra, Juan Manuel (2014)
The approach of the legal, economic, social and political problems that caused the Law of the private pension system in Peru to twenty-two years of its creation is fraught with dissatisfaction in the Peruvian labor force, according to which, at the time of 90, for easy implementation of Decree Law 25897 legal body of labor laws in the country, based on misinformation, ambiguous and misleading advertising was used, which generated the false expectations on the rights of the saver. On the other hand the implemented model AFPs within an autocrat and inquisitor government in the 90s, many extortions, threats and abuses workers were committed, including workers’ signatures were falsified to affiliate to a particular AFP, ie that the sales force used the model was full of gangsters. Today Peru workers have the opportunity to warn that the state and government of the 90’s Peru lied and kept uninformed for many years; workers in the country today can clearly see the results of deception by the state, in the form, manner and method of performance of its funds given to forced and coercive another way for years, to get penniless financial benefits in relation to enjoyed by investors in the AFP. Reason for today feel the need to rescue the right to sit and rethink the law of compulsory savings by working citizen who obliges with no equity in the distribution of benefits among the actors involved in the fate of the savings workers in the country who propose to address the issue of labor savings to the state, and the advantages and benefits that the law should provide the saver.